CONSULTING AS A TOOL FOR ACCELERATING THE ECONOMIC POTENTIAL OF THE BEAUTY INDUSTRY: IMPACT ON EMPLOYMENT DYNAMICS AND OVERCOMING START-UP BARRIERS - Блажко, Катерина (SWorldJournal, 2026)
The article examines the role of professional consulting in unlocking the projected macroeconomic potential of the beauty industry. Official forecasts (U.S. Bureau of Labor Statistics) indicate steady employment growth in the sector at approximately 5% an